Nontoxic electron collimators. Issue 10 (4th September 2021) - Breitkreutz, Dylan Yamabe; Skinner, Lawrie; Lo, Stephanie; Yu, Amy
Abstract: Purpose: The goal of this work was to develop and test nontoxic electron collimation technologies for clinical use. Methods: Two novel technologies were investigated: tungsten‐silicone composite and 3D printed electron cutouts. Transmission, dose uniformity, and profiles were measured for the tungsten‐silicone. Surface dose, relative dose output, and field size were measured for the 3D printed cutouts and compared with the standard cerrobend cutouts in current clinical use. Quality assurance tests including mass measurements, Megavoltage (MV) imaging, and drop testing were developed for the 3D printed cutouts as a guide to safe clinical implementation. Results: Dose profiles of the flexible tungsten‐silicone skin shields had an 80–20 penumbra values of 2–3 mm compared to 7–8 mm for cerrobend. In MV transmission image measurements of the tungsten‐silicone, 80% of the pixels had a transmission value within 2% of the mean. An ∼90% reduction in electron intensity was measured for 6 MeV and a 6.4 mm thickness of tungsten‐silicone and 12.7 mm thickness for 16 MeV. The maximum difference in 3D printed cutout versus cerrobend output, surface dose, and full width at half‐maximum (FWHM) was 1.7%, 1.2%, and 1.5%, respectively, for the 10 cm × 10 cm cutouts. Conclusions: Both flexible tungsten‐silicone and 3D printed cutouts were found to be feasible for clinical use. The flexible tungsten‐silicone was of adequate density, flexibility, and uniformity to serve as skin shields for electron therapy. The 3D printed cutouts were dosimetrically equivalent to standard cerrobend cutouts and were robust enough for handling in the clinical environment.